Teologi Kasih dan Pembinaan Spiritual sebagai Fondasi Pembentukan Karakter Anak di Panti Asuhan Batu Penjuru Yogyakarta - Eunike Nova Dwi Floren Rindani Nussy; Ofri Yunus Sapya (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2026)
Character formation of children in orphanages often faces various challenges, particularly the absence of family figures, experiences of loss, and the need for continuous spiritual guidance. In practice, child care services tend to focus on meeting physical needs and providing formal education, while theological and spiritual aspects have not been optimally utilized as the foundation for character formation. This condition indicates the need for a formative approach rooted in Christian theology, especially the theology of love and spiritual formation. This study aims to analyze the role of the theology of love and spiritual formation as the foundation for character development of children at Batu Penjuru Orphanage, Yogyakarta. This study employs a qualitative method with a descriptive-analytical approach through observation, and interviews with caregivers. The findings reveal that the implementation of the theology of love through accepting relationships, pastoral care, and caregivers’ role modeling, as well as spiritual formation through prayer, worship, biblical teaching, and the habituation of Christian values, contributes to the development of children’s character, including love, responsibility, discipline, and social sensitivity. In conclusion, the theology of love and spiritual formation serve as effective and relevant foundations for character formation in orphanage contexts. The implications of this study emphasize the importance of consistently integrating the theology of love and spiritual formation into child development models in order to cultivate Christian character marked by faith, integrity, and spiritual resilience. Keywords: theology of love; spiritual formation; character formation; orphanage.